US CONTINENTAL NUCLEAR TESTS CONDUCTED DURING 1961–1992 : STATISTICAL ANALYSIS - Wasim, M.; Arif, M.; Zaidi, J. H. (The Nucleus, 2010)
The paper presents statistical analysis of the data obtained from US continental nuclear tests conducted during 1961 - 1992. The analysis summarizes the types of tests, their yield, radioactivity released and the radionuclides emitted during the tests. The application of principal component analysis shows that some radionuclides are emitted in correlation with other radionuclides, which need not originate from the same decay chain. The overall analysis puts emphasis on the detection of radioiodines and radioxenons both for event screening and for event backtracking.